CHARACTERISTICS OF COMPLIMENT RESPONSES BY JAPANESE LEARNERS IN INDONESIA - Bayu Aryanto; Syamsul Hadi; Tatang Hariri (LITERA, 2021)
AbstractResponding to compliments has the potential to cause a polemic for its speakers. Either responding with acceptance at the risk that it would be considered as arrogant or responding with rejection at the risk of disrespecting the interlocutor's opinion of the compliment’s content is where the polemic lies. How Japanese language learners in Indonesia respond to complimentary speech acts is the question addressed in this research. This research is a descriptive study aimed at finding the characteristics of responses given by Japanese language learners in Indonesia to complementary speech acts. The respondents are Japanese language learners with Javanese backgrounds, currently studying at university level in Central Java and Yogyakarta. Data obtained from 53 respondents resulted in 636 speeches of compliment responses obtained using the ODCT. Based on the results of the data analysis, acceptance responses to compliments were found to be very high, reaching 65 percent of all data. Subsequently, an interesting finding was revealed in the context of compliment pertaining to ability in every context of relationship between the speech participants, wherein most of the respondents rejected the compliment in the respective relationship context, which differs with the context of compliments pertaining to appearance, possession, and personal traits. Keywords: compliment, compliment response, acceptance, rejection, deflection Merespon tuturan pujian berpotensi menimbulkan polemik bagi penuturnya. Apakah ditangapi dengan penerimaan dengan resiko akan dianggap sombong atau ditanggapi dengan penolakan dengan resiko dianggap tidak menghargai pendapat mitra tutur terhadap isi pujian. Dalam masyarakat Jepang, tanggapan tuturan pujian berupa penolakan dinilai sebagai sebuah “kebiasaan”. Namun demikian, bagaimana tuturan pujian ditanggapi oleh para pembelajar bahasa Jepang di Indonesia. Penelitian ini merupakan penelitian deskriptif yang bertujuan untuk menemukan karakteristik tanggapan pujian pembelajar bahasa Jepang di Indonesia. Respondennya merupakan pembelajar bahasa Jepang dengan latar belakang sebagai orang Jawa, dan sedang menempuh pendidikan di tingkat universitas di area Jawa Tengah dan Yogyakarta. Data yang diperoleh dari 53 orang responden tersebut menghasilkan 636 tuturan tanggapan pujian yang diperoleh dengan metode ODCT (oral-discourse completion task). Berdasarkan hasil analisis terhadap data, diperoleh temuan diantaranya tanggapan penerimaan terhadap tuturan pujian sangat tinggi, mencapai 65 persen dari keseluruan data. Kemudian, temuan yang menarik adalah pada konteks isi tuturan pujian terhadap kemampuan di tiap konteks hubungan antar peserta tutur (hubungan simetris, hubungan asimetris-dekat, dan hubungan asimetris-jauh) tuturan penolakan merupakan jawaban terbanyak pada masing-masing konteks tersebut, dan hal tersebut berbeda dengan konteks tuturan pujian terhadap penampilan, kepemilikan, dan perilaku individuKata kunci: tuturan pujian, tanggapan pujian, penerimaan, penolakan, pengalihan